The use of modern means in the realization of the Islamic manuscripts Preparation (Journal of the College of Basic Education, 2019)
I wrote a search for the concept of investigation And the use of modern scientific methods in the realization of Islamic manuscripts Since the achievement of manuscripts is very important Because of their effect on the presentation of the manuscript in accordance with customary conditions Prepared for their achievement and directed to the scientific library Those who address the investigation must have special qualities that qualify them to carry out this difficult task His investigation, investigation, honesty, honesty, patience, probity and love for investigation